Generals of the Army : Marshall, MacArthur, Eisenhower, Arnold, Bradley - Willbanks, James H., 1947- (Book collections on Project MUSE., 2013)
"Formally titled "General of the Army," the five-star general is the highest possible rank awarded in the U.S. Army in modern times and has been awarded to only five men in the nation's history: George C. Marshall, Douglas MacArthur, Dwight D. Eisenhower, Henry H. Arnold, and Omar N. Bradley. In addition to their rank, these distinguished soldiers all shared the experience of serving or studying at Fort Leavenworth, Kansas, where they gained the knowledge that would prepare them for command during World War II and the Korean War. In Generals of the Army, James H. Willbanks assembles top military historians to examine the connection between the institution and the success of these exceptional men. Historically known as the "intellectual center of the Army," Fort Leavenworth is the oldest active Army post west of Washington, D.C., and one of the most important military installations in the United States. Though there are many biographies of the five-star generals, this innovative study offers a fresh perspective by illuminating the ways in which these legendary figures influenced and were influenced by Leavenworth. Coinciding with the U.S. Mint's release of a series of special commemorative coins honoring these soldiers and the fort where they were based, this concise volume offers an intriguing look at the lives of these remarkable men and the contributions they made to the defense of the nation."--Publisher's website